The wedding singer [videorecording (Blu-Ray)] - Grey, Brad, 1957-2017; Simonds, Robert, 1964-; Giarraputo, Jack; Herlihy, Tim; Coraci, Frank; Sandler, Adam; Barrymore, Drew; Taylor, Christine, 1971-; Dilbeck, Michael (Distributed by Warner Home Video, 2009)
Robby is stood up at the altar by Linda, who has decided that the prospect of marrying a guy whose only job is to sing at wedding receptions and that it doesn't equal the attraction she felt when he was lead singer in a rock band. Robby finds consolation in his friendship with Julia, a waitress at the wedding receptions and bar mitzvahs where he performs. Julia asks Robby to help her plan her upcoming wedding to Glenn, because he isn't interested in the details of the ceremony. Robby learns that Glenn isn't that interested in Julia and is marrying her because she 'deserves it' since she stuck with him for years, plus he knows she's not marrying him for his money. Now, Robbie has to decide if he wants to keep living with his sister or start a new life with Julia.